2006
DOI: 10.1080/01919510601039726
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Oxidation of Endocrine Disruptors and Pharmaceuticals in Surface Water and Wastewater

Abstract: The oxidative removal of a diverse group of trace organic contaminants from surface water and wastewater was evaluated using ozone (O 3 ) and O 3 combined with hydrogen peroxide (O 3 /H 2 O 2 ). Target compounds included estrogenic and androgenic steroids, pharmaceuticals, pesticides, and industrial chemicals. Bench-and pilot-scale experiments were conducted with surface water spiked with the target compounds and wastewater effluent containing ambient concentrations of target compounds. Full-scale water treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(161 citation statements)
references
References 42 publications
15
133
1
5
Order By: Relevance
“…34,40,52,71,72 Similar to observations with MBRs, available data indicate a slight increase in the extent of PPCP removal when sand filtration is used for post-secondary treatment (Fig. 6).…”
Section: B1 Membrane Bioreactors (Mbrs)supporting
confidence: 71%
See 3 more Smart Citations
“…34,40,52,71,72 Similar to observations with MBRs, available data indicate a slight increase in the extent of PPCP removal when sand filtration is used for post-secondary treatment (Fig. 6).…”
Section: B1 Membrane Bioreactors (Mbrs)supporting
confidence: 71%
“…7 includes PPCP data from a full-scale treatment facility incorporating BAC for tertiary treatment. 72 Although the system displayed good removal for several PPCPs, more work is needed to understand the design and operational parameters influencing PPCP removal by BAC.…”
Section: Compound (Cas #)mentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of DEET enters waterways via sewage effluent following washing off and absorption/excretion by humans; almost 20% is adsorbed through skin, metabolized or excreted (Sudakin et al, 2003). Even if DEET can be efficiently abated through advanced oxidation processes (AOPS) methods such as Fenton (Zhang et al, 2006;Zhang et al, 2007) and ozone treatment (Snyder et al, 2006), it was found at trace level in surface waters, groundwater and waters for human consumption (Sandstrom et al, 2005;Kolpin et al, 2004;Langford et al, 2008;Costanzo et al, 2007). DEET presence was detected in USA rivers, at an average concentration of 0.05 μg/L (Sandstrom et al, 2005); into 97% of surface waters in Australian Eastern coast at an average concentration of 0.093μg/L (Costanzo et al, 2007); in Europe, across river Rhine at concentration ranging from 15 to 30 ng/L (Schwarzbauer et al, 2005 Quednow and Püttmann, 2009), across Norway coast at concentrations 0.4-13 ng/L (Langford et al, 2008;Weigel et al, 2004), and in the North Sea, where it is considered as a ubiquitous pollutant with an average concentration of 1.1 ng/L in summertime (Weigel et al 2002).…”
Section: Introductionmentioning
confidence: 99%